2022
DOI: 10.3390/min12091112
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Prospecting Target Based on Selective Transfer Network

Abstract: In recent years, with the integration and development of artificial intelligence technology and geology, traditional geological prospecting has begun to change to intelligent prospecting. Intelligent prospecting mainly uses machine learning technology to predict the prospecting target area by mining the correlation between geological variables and metallogenic characteristics, which usually requires a large amount of data for training. However, there are some problems in the actual research, such as fewer geol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…Deep learning has been actively applied in geological information metallogenic prediction and has achieved many innovative results [9][10][11][12][13][14]. Zuo and Carranza [15] used the SVM algorithm to predict the Nova Scotia gold deposit in western Canada, which confirmed that the SVM algorithm has obvious advantages in prediction accuracy and precision compared with the traditional weight of evidence method.…”
Section: Literature Review 21 Deep Learning For Metallogenic Predictionmentioning
confidence: 96%
See 1 more Smart Citation
“…Deep learning has been actively applied in geological information metallogenic prediction and has achieved many innovative results [9][10][11][12][13][14]. Zuo and Carranza [15] used the SVM algorithm to predict the Nova Scotia gold deposit in western Canada, which confirmed that the SVM algorithm has obvious advantages in prediction accuracy and precision compared with the traditional weight of evidence method.…”
Section: Literature Review 21 Deep Learning For Metallogenic Predictionmentioning
confidence: 96%
“…The probability distribution after using softmax is, P = {P i } k i=1 , P i = [P 0 , P 1 ], where P 0 is the probability predicted to be "ore free" and P 1 is the probability predicted to be "ore present". We obtain the prediction results of each channel network through Formula (10) and determine the final prediction results through the vote of Formula (11). ŷi = argmax(P i )…”
Section: Fully Connected Layer Softmax and Votingmentioning
confidence: 99%